Jigsaw Cooperative Learning Strategy In Islamic Religious Education Subjects - Saeful Anwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Strategy is planning, steps and sequences to achieve a goal, so in learning educators must make a plan, steps in achieving goals . One of the effective learning strategies applied is the Jigsaw cooperative learning strategy. This research was made to determine the effectiveness of the implementation method application of Jigsaw cooperative learning in class VIII Islamic religious education subjects at SMP Negeri 3 Lelea, Indramayu Regency and to find out the benefits of Jigsaw cooperative learning strategies for educators and students. This research was conducted using qualitative methods with case studies at SMP Negeri 3 Lelea, Indramayu Regency. The data collection techniques used by researchers are interviews, observation, and documentation. However, because of the pandemic that is currently sweeping the world, researchers are focusing more on research on primary and secondary data by using basic books to clarify primary data and interviews with primary data sources, namely Islamic religious education teachers, and several students. The conclusion of this study is that the application of the learning process using Jigsaw cooperative learning in Islamic religious education subjects in class VIII SMP Negeri 3 Lelea Indramayu when the learning process takes place using this learning during online learning, Jigsaw learning becomes effective, students are more active , and there are several obstacles in implementing it online, including internet signal problems and group division. Learning by using Jigsaw cooperative learning has benefits, including benefits for educators, namely it is easier to teach students to respect the opinions of others, trust each other, share opinions and help each other, benefits for students. The benefits for students, one of which is that they can improve their learning achievement when learning to use the Jigsaw cooperative learning model.